Kemampuan Berpikir Kreatif Matematis dan Resiliensi Matematis - Sari, Rizki Agustina; Untarti, Reni (Mandalika Mathematics and Educations Journal, 2021)
AbstractMathematical creative thinking ability is a critical ability in learning mathematics, especially in solving mathematical problems. This research is a qualitative descriptive study that aims to describe the mathematical creative thinking skills based on the mathematical resilience of grade VII F students of SMP Negeri 1 Banyumas. The research subjects were grouped into 3 categories, namely high, medium, and low mathematical resilience categories. The sampling technique used purposive sampling by taking 3 people each in each category to become respondents. Data collection was done by giving questionnaires, written tests, interviews, and documentation which were carried out online. The data analysis technique was done by reducing the data, presenting the data, and drawing conclusions. The results showed: (1) students in the high mathematical resilience category were able to provide a variety of different solutions, as well as come up with new ideas with systematic and detailed answers, (2) students in the moderate mathematical resilience category were able to provide more than one different solution with systematic answers but not detailed, and (3) students in the low mathematical resilience category can solve mathematical problems with systematic.Keywords: Mathematical Creative Thinking Skills; Mathematical Resilience AbstrakKemampuan berpikir kreatif matematis adalah kemampuan yang penting dalam pembelajaran matematika, terlebih dalam penyelesaian permasalahan matematika. Penelitian ini merupakan penelitian deskriptif kualitatif yang bertujuan untuk mendeskripsikan kemampuan berpikir kreatif matematis berdasarkan pada resiliensi matematis siswa kelas VII F SMP Negeri 1 Banyumas. Subyek penelitian dikelompokkan menjadi 3 kategori, yaitu kategori resiliensi matematis tinggi, sedang, dan rendah. Teknik pengambilan sampel menggunakan purposive sampling dengan mengambil masing –masing 3 orang pada setiap kategori untuk dijadikan responden. Pengumpulan data dilakukan dengan pemberian angket, tes tertulis, wawancara, dan dokumentasi yang dilakukan secara online. Teknik analisis data dilakukan dengan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan: (1) siswa kategori resiliensi matematis tinggi mampu memberikan berbagai penyelesaian berbeda, serta memunculkan ide baru dengan jawaban yang sistematis dan terperinci, (2) siswa kategori resiliensi matematis sedang mampu memberikan lebih dari satu penyelesaian yang berbeda dengan jawaban yang sistematis namun tidak rinci, dan (3) siswa kategori resiliensi matematis rendah mampu menyelesaikan permasalahan matematika dengan jawaban yang sistematis.Kata Kunci: Kemampuan Berpikir Kreatif Matematis; Resiliensi Matematis